Principales labores de empaque en banano (Musa paradisiaca AAA) de exportación en la Finca Aurora – Vinces – Los Ríos - Andrade Zamora, Ramón Antonio (2021)
Banana is an emblematic crop in our canton, since it generates jobs and direct and indirect income for families. The present research work called Main packaging tasks in bananas (Musa × paradisiaca) for export at the Aurora - Vinces - Los Ríos farm. For the preparation of this thesis, 1 farms whose name is La Aurora was chosen, it was determined that due to the agricultural work that is given to bananas, 600 boxes per week are harvested in 9 Ha. The following agricultural tasks are carried out in the packing house such as receive fruits, fruit sampling, remove urethane sponge, deflower, creaminess, excesses, hand pick, fumigation, sealing, packing, weighing, quality control and stowage